2016
DOI: 10.1177/1363459315611870
|View full text |Cite
|
Sign up to set email alerts
|

The consent process: Enabling or disabling patients’ active participation?

Abstract: Standards expected by doctors’ regulatory bodies in respect of the process of consent to treatment have arguably sought to restructure the nature of the doctor–patient relationship from one of the paternalism to that of shared decision-making. Yet, few studies have explored empirically, from patients’ perspectives, the extent to which the process of consent to treatment enables or disables patients’ participation in medical decision-making. Our article examines patients’ attitudes towards the consent process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…These narratives suggest that an individual’s very desire/desperation to participate in a trial may render them vulnerable to suggestion, which in turn disrupts the equipoise deemed essential for ethical consent-gaining and hence for effective randomisation [10]. Such imbalances in decision-making parallel those seen in treatment decision-making in general healthcare [30, 31] and other clinical trials [16, 17], and create an ethical challenge for trial managers and recruitment personnel worthy of further enquiry.…”
Section: Discussionmentioning
confidence: 99%
“…These narratives suggest that an individual’s very desire/desperation to participate in a trial may render them vulnerable to suggestion, which in turn disrupts the equipoise deemed essential for ethical consent-gaining and hence for effective randomisation [10]. Such imbalances in decision-making parallel those seen in treatment decision-making in general healthcare [30, 31] and other clinical trials [16, 17], and create an ethical challenge for trial managers and recruitment personnel worthy of further enquiry.…”
Section: Discussionmentioning
confidence: 99%
“…For patients this orally conveyed information is central which they relate to in retrospect, despite comprehensive written material given to them. 7,13 Therefore, physician-researchers should be aware of the kind of communication patterns they use and of the implications for patients. By becoming aware of the used communication patterns for motivating patients to research participation, those patterns can be identified which are ethically acceptable and could then be deliberately implemented in this research context.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the consent procedure for the biomarker study constituted a constantly repeating act, which means that patients perceive it as a form of paternalistic and bureaucratic routine rather than a session catering to their benefit. 13 Physicians but also ethics committees still seem to incorrectly assume that patients will acquire information by means of written material. Previous research has found that most patients do not fully read the informed consent information material because they are content with signing the consent form after being provided with verbal information by the physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informed consent (IC) is imperative and necessary prior to lots of patients' medical treatments, Despite its critical importance to the provision of safe, high-quality, patient-centered health care, practical problems remain in the IC process [ 1,7,8]. Prior research has demonstrated that patients' comprehension and recollection of the key elements of IC are often poor [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%